Effects of ischemic preconditioning on maximal constant-load cycling performance - Santos de Oliveira Cruz, R.; Alves de Aguiar, R.; Turnes, T.; Pereira, K. L.; Caputo, F. (Journal of Applied Physiology, 2015)
This study investigated the effects of ischemic preconditioning (IPC) on the ratings of perceived exertion (RPE), surface electromyography, and pulmonary oxygen uptake (VO2) onset kinetics during cycling until exhaustion at the peak power output attained during an incremental test. A group of 12 recreationally trained cyclists volunteered for this study. After determination of peak power output during an incremental test, they were randomly subjected on different days to a performance protocol preceded by intermittent bilateral cuff pressure inflation to 220 mmHg (IPC) or 20 mmHg (control). To increase data reliability, the performance visits were replicated, also in a random manner. There was an 8.0% improvement in performance after IPC (control: 303 s, IPC 327 s, factor SDs of ×/÷1.13, P = 0.01). This change was followed by a 2.9% increase in peak VO2 (control: 3.95 l/min, IPC: 4.06 l/min, factor SDs of ×/÷1.15, P = 0.04), owing to a higher amplitude of the slow component of the VO2 kinetics (control: 0.45 l/min, IPC: 0.63 l/min, factor SDs of ×/÷2.21, P = 0.05). There was also an attenuation in the rate of increase in RPE (P = 0.01) and a progressive increase in the myoelectrical activity of the vastus lateralis muscle (P = 0.04). Furthermore, the changes in peak VO2 (r = 0.73, P = 0.007) and the amplitude of the slow component (r = 0.79, P = 0.002) largely correlated with performance improvement. These findings provide a link between improved aerobic metabolism and enhanced severe-intensity cycling performance after IPC. Furthermore, the delayed exhaustion after IPC under lower RPE and higher skeletal muscle activation suggest they have a role on the ergogenic effects of IPC on endurance performance.